Nonlinear Analysis of Electrically-coupled Microbeams under Mechanical Shock - Ahmed, Moustafa Adel Sayed (2018)
A Master of Science thesis in Mechanical Engineering by Moustafa Adel Sayed Ahmed entitled, “Nonlinear Analysis of Electrically-coupled Microbeams under Mechanical Shock”, submitted in April 2018. Thesis advisor is Dr. Mehdi Ghommem. Soft and hard copy available.